1996
DOI: 10.1007/bf00182059
|View full text |Cite
|
Sign up to set email alerts
|

Human urinary bladder-carcinoma cells are non-osteoinductive

Abstract: Small pieces (ca. 2-3 x 3-5 mm) of the urinary-tract mucosa from noninvasive papillary transitional-cell carcinomas of the bladder (ca. urotheliale papillare, n = 33), invasive transitional-cell carcinomas of the bladder (ca. urotheliale papillare infiltrans, n = 6, papillary transitional-cell carcinomas of the bladder with squamous metaplasia (ca. urotheliale papillare cum metaplasia planoepitheliale, n = 4), transitional-cell carcinomas in situ (ca. urotheliale in situ, n = 2), and squamous-cell carcinomas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…15 There have been numerous studies demonstrating the ability of transplanted urinary bladder epithelium to induce bone formation in soft tissues. [15][16][17] This phenomenon has been studied and produces consistent results in dogs, cats, rabbits, gerbils and guinea pigs. 16 17 Histopathology in this patient demonstrated foci of immature woven bone lined by a single layer of plump well-differentiated osteoblasts.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…15 There have been numerous studies demonstrating the ability of transplanted urinary bladder epithelium to induce bone formation in soft tissues. [15][16][17] This phenomenon has been studied and produces consistent results in dogs, cats, rabbits, gerbils and guinea pigs. 16 17 Histopathology in this patient demonstrated foci of immature woven bone lined by a single layer of plump well-differentiated osteoblasts.…”
Section: Discussionmentioning
confidence: 71%
“…The requirements of bone induction include the presence of osteogenic precursor cells (including mesenchymal cells distributed in normal tissues), the presence of inducing agents and an environment permitting osteogenesis such as muscle and fascia 15. There have been numerous studies demonstrating the ability of transplanted urinary bladder epithelium to induce bone formation in soft tissues 15–17. This phenomenon has been studied and produces consistent results in dogs, cats, rabbits, gerbils and guinea pigs 16 17.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Only in 4 out of 47 cases of carcinoma urotheliale papillare examined was a small amount of calcifying carti lage, present in only a few serial sections, found. A detailed histological analysis of these 4 cases showed that the cartilage was present in the stroma of grafted tumor, rather than in the graft-surrounding area [21], Moreover, the pathologists did not report the presence of cartilage/ bone in the stroma of routine tumor biopsies. Thus, these cases should not be considered as an example of bone induction by human urothelium but merely as a stromal osseous metaplasia of the grafted tumor.…”
Section: Discussionmentioning
confidence: 99%